Pollution Severity Monitoring of High Voltage Transmission Line Insulators Using Wireless Device Based on Leakage Current Bursts - Osama E. Gouda; Mohamed M. F. Darwish; Karar Mahmoud; Matti Lehtonen; Tamer M. Elkhodragy (IEEE Access, 2022)
The present article describes a smart wireless online device for the severity monitoring of the contaminated insulators of high voltage transmission networks. Accordingly, the wireless developed monitor works by continuously sensing the magnitudes of the leakage current bursts and calculating its average root-mean-square (RMS) value for every second or minute as the monitor software is calibrated. Regarding, if the average of the leakage current RMS value is adjudicated by the monitor as corresponding to a probably significant scale of a power outage, the monitor transfers an alarm signal and sends a warning message to the maintenance crew members to take the action to wash the high voltage line insulators on time before the unexpected outage of the high voltage network has been occurring. The developed monitor contains the following main units: current transformer with burden resistor, Node MCU (ESP8266), solar power bank, cloud-based data storage, and smart device (Mobile or tablet). These units can be assembled to work without the need for a power source. The proposed monitor has many merits over the other monitoring devices; it enjoys little cost, easy of handling, and calibration. It has a high degree of safety, it is an online system, and its design is simple. The developed monitor is tested in the Laboratory using insulators with different pollution layers’ conductivity and the findings show that the accuracy of the proposed monitor reached 91.66 % after carrying out 50 tests.